Practicing Responsibility in Business Schools Implications for Teaching, Research, and Innovation - Asheim, Bjørn T.; Laudal, Thomas; Mykletun, Reidar J. (Edward Elgar Publishing, 2023)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Promoting more responsible action in relation to business sustainability, this book addresses the increasing discomfort among faculty members and wider society as to how business schools prepare students for the future. Reflective and inspiring, it seeks to motivate the necessary action which may be a small but crucial catalysts to solving challenges posed by increasing globalisation, migration, economic development, changing demographics, and cultural exchange.